Structural and mutational analysis of member-specific STAT functions - Erdogan, Fettah; Qadree, Abdul K.; Radu, Tudor B.; Orlova, Anna; de Araujo, Elvin D.; Israelian, Johan; Valent, Peter; Mustjoki, Satu M.; Herling, Marco; Moriggl, Richard; Gunning, Patrick T. (Biochimica et biophysica acta. General subjects, 2022)
The STAT family of transcription factors control gene expression in response to signals from various stimulus. They display functions in diseases ranging from autoimmunity and chronic inflammatory disease to cancer and infectious disease. This work uses an approach informed by structural data to explore how domain-specific structural variations, post-translational modifications, and the cancer genome mutational landscape dictate STAT member-specific activities. We illustrated the structure-function relationship of STAT proteins and highlighted their effect on member-specific activity. We correlated disease-linked STAT mutations to the structure and cancer genome mutational landscape and proposed rational drug targeting approaches of oncogenic STAT pathway addiction. Hyper-activated STATs and their variants are associated with multiple diseases and are considered high value oncology targets. A full understanding of the molecular basis of member-specific STAT-mediated signaling and the strategies to selectively target them requires examination of the difference in their structures and sequences. •Hyper-activated STATs are a high value oncology pharmacologic target.•Domain-specific variations dictate STAT member-specific activities.•STAT structural data illuminates mechanism of disease-linked STAT mutations.•Member-specific STAT activity is guided by post-translational modifications.